STUDY OF THE IMPACT OF LAND USE CHANGES ON FLOOD DISPOSAL OF THE MOLIBAGU RIVER, SOUTH BOLAANG MONGONDOW REGENCY NORTH SULAWESI PROVINCE - Marcellino Oroh, Ficky
South Bolaang Mongondow Regency is one of the regencies in North Sulawesi which experiences flooding almost every year. flood discharge and cause water to overflow during the rainy season. The purpose of this research is to calculate the design discharge using the SCS CN method with the help of the HEC-HMS application and to model inundation height, flood depth, using HEC-RAS 2D software, and map flood risk using GIS software in the Molibagu watershed. Both were calibrated using the HEC-HMS application and got close to the SCS CN method. Based on the analysis of one of the natural factors that caused flooding in the research area, namely high rainfall in 2011 was 62 mm and in 2020 was 192 mm. Based on the results of the hydrological analysis using the HEC-HMS application with the SCS CN method, the discharge at the Molibagu water guess in 2011 and 2020 after calibration and after the analysis recorded the Molibagu watershed for 2 years, 5 years, 10 years, 25 years, 50 years and 100 years of peak/maximum discharge 44.416 (m3/s), 101.157 (m3/s), 149.811(m3/s), 218.274 (m3/s), 272.959 (m3/S) and 329.801 (m3/s) with runoff volume The advantages are 18.639 mm, 39.244 mm, 56.949 mm, 81.398 mm, 101.684 mm and 123.069 mm. Year 2020 at 2 years, 5 years, 10 years, 25 years, 50 years and 100 years of peak/maximum discharge 82.424 (m3/s), 189.628 (m3/s), 275.534 (m3/s), 403.352 (m3/s), 505.416 (m3/s), 611.474 (m3/s) with a runoff volume of 31.949 mm, 71.826 mm, 103.622 mm, 148.096 mm, 183.443 mm, 220.096 mm. Parameters Molibagu watershed has a CN value and a drainage coefficient C that affects flood discharge, namely for 2011 it has a value of CN 42.04 and a Flow Coefficient of C has a value of 0.412 and 2020 has a value of CN 42.20 and a coefficient of Flow C has a value of 0.415. Analysis of flood vulnerability maps In 2011 the Molibagu watershed has a high vulnerability, namely Molibagu village with an area of 0.11 km2, moderate vulnerability namely Sogou Village, Toluaya Village and Popodu Village with an area of 0.42 km2, and low vulnerability namely East Salongo Village 0.01 km2. Flood vulnerabilities in 2020 that have high vulnerability are Soguo Village, Toluaya Village and Molibagu Village with an area of 1.96 km2 and medium vulnerability are Popodu Village, Salongo Timur Village, and Pintandia Village with an area of 0.26 km2.